2004
DOI: 10.1046/j.1439-0426.2003.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diet and stocking density on the growth and behaviour of pond pre-reared pikeperch under intensive conditions

Abstract: Experiments were carried out between 1999 and 2001 on pikeperch fingerlings using two feeds at four stocking densities to evaluate the success of training 35-day-old pond-reared pikeperch, Stizostedion lucioperca L., to lifeless feed in intensive culture. Training periods of 28 days for each of three cohorts (1999)(2000)(2001) were applied to introduce pikeperch from zooplankton to minced feed. In a preliminary study (1999), two feeds (live prey and minced fish meat) were compared at two stocking densities. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…In the first experiment feeds of different fat content were tested comparing growth performance, conversion and total body composition of juvenile pikeperch. Although higher numbers of fish are used in similar experiments to evaluate growth rate and feed utilization, stocking densities used in these experiments makes the results comparable with other studies (Molnár et al. 2004a,b; Zakęś et al.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the first experiment feeds of different fat content were tested comparing growth performance, conversion and total body composition of juvenile pikeperch. Although higher numbers of fish are used in similar experiments to evaluate growth rate and feed utilization, stocking densities used in these experiments makes the results comparable with other studies (Molnár et al. 2004a,b; Zakęś et al.…”
Section: Introductionsupporting
confidence: 73%
“…), European perch Perca fluviatilis L. and also pikeperch Sander lucioperca L. Pikeperch is a traditionally cultured carnivore in the European semi‐intensive pond polyculture system but the intensive production of this species was also widely investigated in the last years (Hilge & Steffens 1996; Zakęś 1997a,b; Zakęś & Karpinski 1999; Ljungreen et al. 2003; Molnár et al. 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Bite marks could often be observed on dead fish. Similarly, Molnar et al. (2004) reported higher mortalities of 50.4–55.8% in pike perch reared at different stocking densities.…”
Section: Discussionmentioning
confidence: 77%
“…Bite marks could often be observed on dead fish. Similarly, Molnar et al (2004) reported higher mortalities of 50.4-55.8% in pike perch reared at different stocking densities. Although apparent physical EFA-deficient signs such as fin erosion and bacterial disease (Sargent et al, 1995(Sargent et al, , 1999 were not observed in any groups during the feeding trial, the best growth was observed in S. hasta fed the iced fish and the pelleted diet, respectively ( Table 2), indicating that iced fish rich in n-3 highly unsaturated FA (HUFA), especially EPA and DHA, had better nutritional values than that of 18:2n-6 and 18:3n-3 FAs for juvenile S. hasta, similar to other reports (Kalogeropoulos et al, 1992;Wilson and Moreau, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…One important factor influencing fish growth heterogeneity is the stocking density (Zoccarato et al., 1992; Jørgensen et al., 1993; Irwin et al., 1999), but the effects of stocking density are debated. On the one hand, some researchers have reported a negative relationship between stocking density and growth, such as in Chinook salmon (Martin and Wertheimer, 1989), gilthead sea‐bream Sparus aurata L. (Canario et al., 1998), and Acipenser schrenckii (Li et al., 2004); whereas other researchers have found that growth was not affected by the stocking density (Molnar et al., 2004; Celikkale et al., 2005), or that it was slower among fish stocked at lower rather than higher densities (Baras et al., 1998). In this study, the similar case of density‐independent categories was found between stocking density and growth of lenok juveniles, although the mean SGR of each group was different (mean SGR was calculated to be 4.90%, 4.37%, 4.37% and 3.98% for the 5, 25, 50 and 75 fish L −1 , respectively).…”
Section: Discussionmentioning
confidence: 99%